Fulvestrant 500 mg versus anastrozole 1 mg for hormone receptor-positive advanced breast cancer (FALCON): an international, randomised, double-blind, phase 3 trial - Robertson, John F.R.; Bondarenko, Igor M.; Trishkina, Ekaterina; Dvorkin, Mikhail; Panasci, Lawrence; Manikhas, Alexey; Shparyk, Yaroslav; Cardona-Huerta, Servando; Cheung, Kwok-Leung; Philco-Salas, Manuel Jesus; Ruiz-Borrego, Manuel; Shao, Zhimin; et al. (Elsevier, 2017)
Background